PUSTAKAWAN PROFESIONAL DI ERA DISRUPSI - Rahmawati, Laila (CV. Adiba Aisha Amira, 2024)
The relationship between users and libraries and librarians has undergone a transformation into a complex public space. The complexity of this public space is not only to accommodate interactions between users and librarians in relation to access to information and knowledge, but also as a space for inter-generational, inter-interest, inter-community, inter-professional meetings that unite and interact with librarians, technology, networked and bonded by library collections and library collection documents. Librarians in the era of disruption must be able to develop the competencies needed to achieve success by making various breakthroughs. Libraries must be creative and respond to changes that emerge after disruption, including by adapting to the changes that occur. Facing the era of digital disruption, a librarian needs to develop strategies according to the needs and times to face the changes occurring in the library world. Some strategies that can be implemented include increasing digital literacy, innovating, prioritizing research, providing excellent service, being open to developments in information technology, collaborating with other parties, improving managerial abilities, needing to prioritize constructive innovation, always upgrading one's own competence and acts as a stimulator and trigger in the development of digital content.